Dust exposure in workers from grain storage facilities in Costa Rica - Rodríguez Zamora, María G. (2017)
About 12 million workers are involved in the production of basic grains in Central America. However, few studies in the region have examined the occupational factors associated with inhalable dust exposure. About the objectives: (i) To assess the exposure to inhalable dust in workers from rice, maize, and wheat storage facilities in Costa Rica; (ii) to examine the occupational factors associated with this exposure; and (iii) to measure concentrations of respirable and thoracic particles in different areas of the storage facilities. As for the methods, we measured inhalable (<100 m) dust concentrations in 176 personal samples collected from 136 workers of eight grain storage facilities in Costa Rica. We also measured respirable (<4 m) and thoracic (<10 m) dust particles in several areas of the storage facilities. Now, about the results, Geometric mean (GM) and geometric standard deviation (GSD) inhalable dust concentrations were 2.0 mg/m3 and 7.8 (range = < 0.2–275.4 mg/m3). Personal inhalable dust concentrations were associated with job category [GM for category/GM for administrative staff and other workers (95% CI) = 4.4 (2.6, 7.2) for packing; 20.4 (12.3, 34.7) for dehulling; 109.6 (50.1, 234.4) for unloading in flat bed sheds; 24.0 (14.5, 39.8) for unloading in pits; and 31.6 (18.6, 52.5) for drying], and cleaning task [15.8 (95% CI: 10.0, 26.3) in workers who cleaned in addition to their regular tasks]. Higher area concentrations of thoracic dust particles were found in wheat (GM and GSD = 4.3 mg/m3 and 4.5) and maize (3.0 mg/m3 and 3.9) storage facilities, and in grain drying (2.3 mg/m3 and 3.1) and unloading (1.5 mg/m3 and 4.8) areas. Finally, the conclusions state that operators of grain storage facilities showed elevated inhalable dust concentrations, mostly above international exposure limits. Better engineering and administrative controls are needed.